The Digitization of Islamic Philanthropy: Legal Accountability of Amil Zakat Institutions in Zakat Management via E-Commerce - Hazhin, Utiyafina Mardhati; Sunur, Yosefina Elinda (West Science Law and Human Rights, 2025)
The digitalization of Islamic philanthropy has compelled amil zakat institutions to adapt to technological advancements, including through partnership with e-commerce platforms such as Shopee. While this collaboration facilitates muzakki in fulfilling their zakat obligations, it raises legal questions concerning the accountability of zakat institutions in managing digital zakat funds. This study aims to examine the practice of digital zakat management via e-commerce platforms, the legal relationships among the involved parties, and the form of accountability borne by amil zakat institutions in distributing zakat through digital means. This research employs a normative legal methodology, utilizing statutory and conceptual approaches. The findings indicate that, despite the absence of specific regulations governing zakat through e-commerce, zakat institutions remain fully legally accountable under Law No. 23 of 2011 and Government Regulation No. 14 of 2014. Such accountability encompasses administrative, moral, and social responsibilities. The lack of technical regulations concerning digital zakat transaction mechanisms and standardized reporting indicates weak institutional accountability, potentially undermining public trust in digital zakat practices. Therefore, a regulatory framework is urgently needed one that accomodates digital innovation while ensuring transparency and accountability in accordance with sharia principle.